2021
DOI: 10.1111/asj.13619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorogenic acid on intestinal inflammation, antioxidant status, and microbial community of young hens challenged with acute heat stress

Abstract: Heat stress in poultry is deleterious to productive performance. Chlorogenic acid (CGA) exerts antibacterial, anti-inflammatory, and antioxidant properties. This study was conducted to evaluate the effects of dietary supplemental CGA on the intestinal health and cecal microbiota composition of young hens challenged with acute heat stress. 100-day-old Hy-line brown pullets were randomly divided into four groups.The control group (C) and heat stress group (HS) received a basal diet. HS + CGA 300 group and HS + C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 54 publications
(72 reference statements)
1
21
0
Order By: Relevance
“…In the present study, CGA increased the GSH content in the intestines of immune-stressed broiler breeders, in agreement with Shi [ 30 ], who found that CGA significantly increased GSH levels in liver tissue and reduced oxidative stress. Several studies have noted that CGA significantly enhanced antioxidant activity in broilers [ 11 , 12 , 25 , 26 ] and pigs [ 13 , 31 ], which was in agreement with our findings. The antioxidant effects of CGA were potentially attributed to its chemical structure for direct scavenging of free radicals and activation of endogenous antioxidant defenses against radicals [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, CGA increased the GSH content in the intestines of immune-stressed broiler breeders, in agreement with Shi [ 30 ], who found that CGA significantly increased GSH levels in liver tissue and reduced oxidative stress. Several studies have noted that CGA significantly enhanced antioxidant activity in broilers [ 11 , 12 , 25 , 26 ] and pigs [ 13 , 31 ], which was in agreement with our findings. The antioxidant effects of CGA were potentially attributed to its chemical structure for direct scavenging of free radicals and activation of endogenous antioxidant defenses against radicals [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the conclusions of many studies that CGA has anti-inflammatory activities [ 36 , 37 ]. Supplemental CGA in the feed exhibited significant anti-inflammatory effects by decreasing the expression of IL-1β and TNF-α in heat-stressed broilers [ 12 ], in broilers infected with Clostridium perfringens type A [ 26 ], and in IBV-infected chickens [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CGA is used in chicken feed to change the oxidative stress and damage of the intestinal brush border membrane when the ambient temperature is too high ( 134 ). Heat stress may accelerate the glycolysis and metabolism of broiler chickens after death, decreasing pH after death and an increase in meat cooking loss.…”
Section: Application Of Cga In Foodmentioning
confidence: 99%
“…CGA can decrease the abundance of Lachnospiraceae , Ruminococcaceae , Desulfovibrionaceae , and Erysipelotrichaceae and increase that of Lactobacillaceae and Bacteroidaceae ( 14 ). Significantly, CGA improved the abundance of beneficial bacteria, including Ruminococcaceae UCG-005, Akkermansia , Christensenellaceae R-7_group , and Rikenellaceae RC9_gut_group ( 15 ) and short-chain fatty acid producers such as Faecalibaculum , Romboutsia , Mucispirillum , and Dubosiella ( 16 ). Meanwhile, CGA reduced the abundance of bacteria involved in inflammation, such as Sutterella species and those that cause intestinal dysfunction, such as Escherichia coli and other LPS-producers ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%